Activation of TLR9 signaling suppresses the immunomodulating functions of CD55lo fibroblastic reticular cells during bacterial peritonitis - Jiang, Ting; Li, Yiming; Huang, Xingping; Jayakumar, Preethi; Billiar, Timothy R.; Deng, Meihong (Frontiers in Immunology, 2024)
Fibroblastic reticular cells (FRCs) are a subpopulation of stromal cells modulating the immune environments in health and disease. We have previously shown that activation of TLR9 signaling in FRC in fat-associated lymphoid clusters (FALC) regulate peritoneal immunity via suppressing immune cell recruitment and peritoneal resident macrophage (PRM) retention. However, FRCs are heterogeneous across tissues and organs. The functions of each FRC subset and the regulation of TLR9 in distinct FRC subsets are unknown. Here, we confirmed that specific deletion of TLR9 in FRC improved bacterial clearance and survival during peritoneal infection. Furthermore, using single-cell RNA sequencing, we found two subsets of FRCs (CD55hi and CD55lo) in the mesenteric FALC. The CD55hi FRCs were enriched in gene expression related to extracellular matrix formation. The CD55lo FRCs were enriched in gene expression related to immune response. Interestingly, we found that TLR9 is dominantly expressed in the CD55lo subset. Activation of TLR9 signaling suppressed proliferation, cytokine production, and retinoid metabolism in the CD55lo FRC, but not CD55hi FRC. Notably, we found that adoptive transfer of Tlr9-/--CD55lo FRC from mesenteric FALC more effectively improved the survival during peritonitis compared with WT-FRC or Tlr9-/--CD55hi FRC. Furthermore, we identified CD55hi and CD55lo subsets in human adipose tissue-derived FRC and confirmed the suppressive effect of TLR9 on the proliferation and cytokine production in the CD55lo subset. Therefore, inhibition of TLR9 in the CD55lo FRCs from adipose tissue could be a useful strategy to improve the therapeutic efficacy of FRC-based therapy for peritonitis.